An optimal control approach to considering uncertainties in kinetic parameters in the maintenance scheduling and production of a process using decaying catalysts. (June 2021) - Adloor, S.D.; Vassiliadis, V.S.
Highlights: Novel solution methodology obviates need for combinatorial optimisation solvers. Multistage optimal control problem formulation with continuous variables only. Kinetic parameter uncertainty handled through multiple scenario approach. Feasible path method enables solution for real-world sized industrial problems. Heavy computational load shifted to embedded dynamic simulation not to optimisation. Abstract: This article presents a novel approach for optimising maintenance scheduling and production in a process using decaying catalysts while considering uncertainties in the kinetic parameters involved. The approach formulates this problem as a multistage mixed-integer optimal control problem (MSMIOCP) and uses a solution methodology that can offer a number of potential advantages over conventional methodologies. The solution methodology involves using a multiple scenario approach to consider parametric uncertainties and formulating a stochastic version of the MSMIOCP, which is solved as a standard nonlinear optimisation problem using a technique developed in a previous work. The proposed formulation and solution methodology are applied to identify the effects on the optimal process operation, of individual uncertainty of each parameter, of simultaneous uncertainty of all parameters and of the number of scenarios generated, as four case studies. The results obtained provide insights into these aspects and indicate the approach's capability to solve this problem.